2016
DOI: 10.1038/srep22633
|View full text |Cite
|
Sign up to set email alerts
|

Dragon kings of the deep sea: marine particles deviate markedly from the common number-size spectrum

Abstract: Particles are the major vector for the transfer of carbon from the upper ocean to the deep sea. However, little is known about their abundance, composition and role at depths greater than 2000 m. We present the first number-size spectrum of bathy- and abyssopelagic particles to a depth of 5500 m based on surveys performed with a custom-made holographic microscope. The particle spectrum was unusual in that particles of several millimetres in length were almost 100 times more abundant than expected from the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 51 publications
(72 reference statements)
0
57
0
2
Order By: Relevance
“…The variability in taxonomic composition of eukaryotic microbes was high in that study with much of the variance explained by water mass (Pernice et al, 2016). As the amount of deep-sea marine snow changes dramatically by water mass and location (Bochdansky et al, , 2016, some of the high variability in microbial eukaryotes is very likely due to the relative abundance and type of marine snow in these layers.…”
Section: Fungimentioning
confidence: 65%
See 4 more Smart Citations
“…The variability in taxonomic composition of eukaryotic microbes was high in that study with much of the variance explained by water mass (Pernice et al, 2016). As the amount of deep-sea marine snow changes dramatically by water mass and location (Bochdansky et al, , 2016, some of the high variability in microbial eukaryotes is very likely due to the relative abundance and type of marine snow in these layers.…”
Section: Fungimentioning
confidence: 65%
“…However, these sediment traps collect fast-sinking particles with much higher efficiency than slowly-sinking particles, while buoyant particles are not collected at all. Recently, we demonstrated that bathypelagic particles in a size range from 400 μm to several mm were more abundant than expected from the number spectrum of smaller particles (Bochdansky et al, 2016). Approximately 30% of these particles did not contain apparent ballast, such as fecal pellets or dense phytodetritus, but a large amount of transparent exopolymer particles (TEP, Alldredge et al, 1993), which led us to conclude that they are either neutrally buoyant or slow sinking (Bochdansky et al, 2016).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations